Medical Experts and Agnotology in the Fumes Controversy of the Huelva Copper Mines (1888–1890). Issue 3 (12th June 2017) - Guillem-Llobat, Ximo
Abstract : Huelva's copper mines (Spain) have been active for centuries but in the second half of the nineteenth century extractive activities in Riotinto, Tharsis, and other mines in the region were intensified in order to reach world leadership. The method used in these mines for copper extraction from low grade ores generated continuous emissions of fumes that were extremely controversial. The inhabitants had complained about the fumes for decades but as activity intensified so did complaints. The killing of anti-fumes demonstrators in 1888 led to the passing of a Royal Decree banning the open-air roasting of ore and to the drafting of numerous reports on the hazards of the fumes. Major state and provincial medical institutions, as well as renowned hygienists and engineers, took part in the assessment, contributing to a scientific controversy especially rich in content. In my paper I will analyse the production and circulation of knowledge and ignorance about the impact of fumes on public health, as well as the role of medical experts and expertise in the controversy. The analysis will focus on the reports drafted between the 1888 ban and its 1890 repeal, and will show the changing nature of the expert assessment and the numerous paths followed by experts in producing ignorance. The paper will conclude by considering other stakeholders, who may shed some light on the reasons behind the performance of the medical experts.